Shear modulus titration in crystalline colloidal suspensions - Palberg, Thomas; Kottal, Johannes; Bitzer, Franz; Simon, Rolf; Würth, Mathias; Leiderer, Paul (My University, 1995)
We present the first direct experimental access to the actual surface charge number Z of colloidal particles under conditions of strong electrostatic interaction. We further calculate a renormalized charge number Z *(Z) using the modified DLVO approximation and the dependence of the shear modulus G(Z*) on the concentration of neutral electrolyte ns. The excellent agreement of predicted and measured values provides an experimental verification of the renormalization concept under variation of the salt concentration. The link between the true surface charge number and experimental results via Z* is extended to the conductivity σ(Z*). On the basis of the number of dissociable surface groups N and numerical solutions of the nonlinearized Poisson-Boltzmann equation we further provide a qualitative model for incomplete dissociation under conditions of overlapping double layers.
Keywords: 530